248 HPV vaccine knowledge and beliefs among women in rural areas - Deborah Smith; Shreveport Cory Coehoorn; Shreveport Robbie A. Beyl; Yanna Xhari Alesafis de Koter; Emily Martinson Dantes; Shreveport Jerry W. McLarty (Journal of Clinical and Translational Science)
Objectives/Goals: To reduce cervical cancer in the USA, it is essential to identify the reasons underlying the low HPV vaccination rates. This study aims to identify knowledge and beliefs about HPV vaccination among women in rural areas. The knowledge gained from this study will directly lead to developing an education tool tailored specifically for women in rural areas. Methods/Study Population: We conducted a cross-sectional study from November 2022 to July 2023. We recruited women (n  =  141) who visited a mobile health unit in rural North Louisiana. The inclusion criteria were women aged 25–64 years who spoke English, had not undergone a total hysterectomy, and had no history of cervical cancer. Data collected included sociodemographic characteristics, sexual history, awareness and knowledge of HPV infection, cervical cancer, genital warts, and HPV vaccination, the perceived risk of acquiring genital HPV infection and developing cervical cancer, and the willingness to receive an HPV vaccine. Descriptive statistics were used to evaluate participant responses. Written informed consent was obtained before completing the self-administered questionnaire. Results/Anticipated Results: Our findings showed significant gaps in HPV vaccine knowledge and uptake. Approximately 40% of the participants were unaware of the HPV vaccine, 96.5% had never received it, and 91.4% had never been offered it. However, 42% indicated a willingness to consider vaccination if it were offered. Factors influencing their decision to vaccinate against HPV included a family history of cervical cancer (44.7%), having multiple sexual partners (48%), and engaging in unprotected sex (61.7%). Furthermore, there was significant uncertainty surrounding the vaccine, with 65.2% of participants unsure about its safety, 66% unaware of potential health risks, and 47.5% uncertain about its effectiveness in preventing HPV. Discussion/Significance of Impact: Our research emphasizes the need for tailored behavioral interventions to address knowledge gaps about the HPV vaccine. Low HPV vaccination rates in rural areas contribute to health disparities in cervical cancer. Implementing educational interventions in healthcare settings can enhance vaccination rates and mitigate the risk of cervical cancer.